Copper / ceramic joint and insulated circuit board

By forming a copper/ceramic bonding body with a controlled Mg solid solution layer, the bonding strength and reliability are improved, addressing the issue of cracking in ceramic members under severe thermal cycles.

JP7647471B2Active Publication Date: 2025-03-18MITSUBISHI MATERIALS CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021152963
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-21
Publication Date
2025-03-18
Estimated Expiration
2041-09-21

AI Technical Summary

Technical Problem

Existing copper/ceramic bonding technologies face challenges in suppressing cracking in ceramic members under severe cooling/heating cycles, which affects the reliability of insulating circuit boards.

Method used

A copper/ceramic bonding body is formed with a Mg solid solution layer at the interface between the ceramic and copper members, where the maximum indentation hardness is controlled between 90 mgf/μm and 150 mgf/μm to prevent excessive rigidity and cracking.

Benefits of technology

This approach enhances the bonding strength and reliability of the copper/ceramic bonded body under cooling/heating cycles, effectively suppressing cracking in ceramic members and maintaining high bonding integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647471000003
    Figure 0007647471000003
  • Figure 0007647471000004
    Figure 0007647471000004
  • Figure 0007647471000005
    Figure 0007647471000005
Patent Text Reader

Abstract

To provide a copper / ceramic joint body that can prevent a ceramic member from cracking even when subjected to a severe thermal cycle, offering superior thermal cycle reliability.SOLUTION: A copper / ceramic joint body 10 is obtained by joining a copper member 12 composed of copper or a copper alloy and a ceramic member 11. At a joint interface between the ceramic member 11 and the copper member 12, a Mg solid-solution layer 31 is formed in which Mg is dissolved in a matrix phase of Cu. In a region E1 from 20 μm to 50 μm from a joint face of the ceramic member 11 to the copper member 12 side, the maximum value of indentation hardness is 90 mgf / μm2 or more and 150 mgf / μm2 or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copper / ceramic bonded body formed by bonding a copper member made of copper or a copper alloy to a ceramic member, and to an insulating circuit board formed by bonding a copper plate made of copper or a copper alloy to a surface of a ceramic substrate. [Background technology]

[0002] In power modules, LED modules and thermoelectric modules, power semiconductor elements, LED elements and thermoelectric elements are bonded to an insulating circuit board having an insulating layer on one side of which a circuit layer made of a conductive material is formed. For example, power semiconductor elements for controlling large amounts of power used to control wind power generation, electric vehicles, hybrid vehicles, and the like generate a large amount of heat during operation. Therefore, as a substrate for mounting these elements, an insulated circuit board has been widely used which includes a ceramic substrate, a circuit layer formed by bonding a metal plate with excellent electrical conductivity to one surface of the ceramic substrate, and a metal layer for heat dissipation formed by bonding a metal plate to the other surface of the ceramic substrate.

[0003] For example, Patent Document 1 proposes an insulating circuit board in which a circuit layer and a metal layer are formed by bonding copper plates to one side and the other side of a ceramic substrate. In Patent Document 1, copper plates are arranged on one side and the other side of a ceramic substrate with an Ag-Cu-Ti brazing material interposed therebetween, and the copper plates are bonded by performing a heat treatment (a so-called active metal brazing method). In this active metal brazing method, a brazing material containing Ti, which is an active metal, is used, so that the wettability between the molten brazing material and the ceramic substrate is improved, and the ceramic substrate and the copper substrate are bonded well.

[0004] Moreover, Patent Document 2 proposes an insulating circuit board in which a ceramic substrate and a copper plate are bonded together using a Cu-Mg-Ti brazing filler metal. In Patent Document 2, the joining is performed by heating at 560 to 800°C in a nitrogen gas atmosphere, and Mg in the Cu-Mg-Ti alloy sublimes and does not remain at the joining interface, and titanium nitride (TiN) is not substantially formed.

[0005] Furthermore, Patent Document 3 discloses an insulating circuit board in which a copper plate and a ceramic substrate are bonded together using Mg. In Patent Document 3, even when terminals and the like are ultrasonically bonded, it is possible to suppress the occurrence of cracks at the bonding interface between the copper plate and the ceramic substrate. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 3211856 [Patent Document 2] Patent No. 4375730 [Patent Document 3] Patent Publication No. 2021-035901 Summary of the Invention [Problem to be solved by the invention]

[0007] Recently, the heat generation temperature of semiconductor elements mounted on insulating circuit boards has tended to increase, and insulating circuit boards are required to have higher thermal cycle reliability than ever before, so that they can withstand severe thermal cycles. Here, as disclosed in Patent Documents 1 and 2, when a copper plate and a ceramic substrate are joined using a joining material containing Ti, which is an active metal, the active metal Ti diffuses to the copper plate side and an intermetallic compound containing Cu and Ti precipitates, which hardens the vicinity of the joining interface, causing cracks in the ceramic member when subjected to thermal cycles, which may reduce thermal cycle reliability.

[0008] Furthermore, as disclosed in Patent Document 3, when a ceramic substrate and a copper plate are bonded using Mg, a Mg solid solution layer in which Mg is dissolved in the Cu matrix is ​​formed at the bonding interface between the ceramic substrate and the copper plate. Therefore, the vicinity of the bonding surface of the copper plate becomes hard due to the solid solution hardening of Mg. Furthermore, a reaction between oxygen present at the bonding interface and Mg may cause Mg oxide to precipitate in the Mg solid solution layer, and this precipitation hardening may further harden the bonding interface. In this way, even when a ceramic substrate and a copper plate are joined using Mg instead of the active metal Ti, the joining interface becomes hard, and there is a risk that the thermal cycle reliability cannot be sufficiently improved.

[0009] The present invention has been made in view of the above-mentioned circumstances, and has an object to provide a copper / ceramic bonded body that is capable of suppressing the occurrence of cracks in the ceramic members even when subjected to severe thermal cycles and has excellent thermal cycle reliability, and an insulated circuit board made of this copper / ceramic bonded body. [Means for solving the problem]

[0010] In order to solve the above-mentioned problems, the copper / ceramic bonded body of the present invention is a copper / ceramic bonded body obtained by bonding a copper member made of copper or a copper alloy to a ceramic member, wherein a Mg solid solution layer in which Mg is dissolved in a Cu matrix is ​​formed at a bonding interface between the ceramic member and the copper member, and the maximum indentation hardness in a region from 20 μm to 50 μm from the bonding surface of the ceramic member toward the copper member is 90 mgf / μm. 2 More than 150mgf / μm 2 It is characterized by being within the following range:

[0011] In the present invention, the indentation hardness H is calculated by measuring the load-displacement correlation when a test load of 5000 mgf is applied using a triangular pyramidal diamond indenter called a Berkovich indenter, which has an inter-edge angle of 114.8° to 115.1°, and calculating it from the following formula: hc=ht-0.75×P / S (ht: indentation depth, P: load, S: contact stiffness (=dP / dh|Pmax), hc: contact depth) Contact area A=24.56×hc 2 Indentation hardness H=P / A

[0012] According to the copper / ceramic bonded body of the present invention, a Mg solid solution layer in which Mg is dissolved in a Cu matrix is ​​formed at the bonding interface between the ceramic member and the copper member, and the maximum indentation hardness in a region extending from the bonding surface of the ceramic member to the copper member by 20 μm to 50 μm is 90 mgf / μm. 2 As described above, the copper in the vicinity of the bonding interface is sufficiently melted to generate a liquid phase, and the ceramic member and the copper member are firmly bonded to each other. On the other hand, the maximum indentation hardness in the aforementioned region is 150 mgf / μm 2 Since the hardness is kept below 0.1%, the vicinity of the bonding interface is not unnecessarily hard, and the occurrence of cracks during thermal cycle loading can be suppressed. As a result, a copper / ceramic bonded body having high bonding strength and particularly excellent thermal cycle reliability can be obtained.

[0013] In the copper / ceramic bonded body of the present invention, the average indentation hardness in a region extending from the bonding surface of the ceramic member to the copper member by 20 μm to 50 μm is 80 mgf / μm. 2 More than 140mgf / μm 2 It is preferable that the content is within the following range: In this case, the average indentation hardness in the region from the joining surface of the ceramic member to the copper member side of 20 μm to 50 μm is 80 mgf / μm. 2 More than 140mgf / μm 2 Since the content is within the following range, the ceramic member and the copper member are reliably and firmly bonded together by Mg, and the bonded interface is further prevented from becoming hard. As a result, a copper / ceramic bonded body having high bonding strength and particularly excellent thermal cycle reliability can be obtained.

[0014] In the copper / ceramic bonded body of the present invention, the average indentation hardness in a region extending from the surface of the copper member bonded to the ceramic member opposite the ceramic member to the ceramic member by 10 μm to 30 μm toward the ceramic member is 70 mgf / μm. 2 More than 85mgf / μm 2 It is preferable that the content is within the following range: In this case, the average indentation hardness in a region of the copper member that is 10 μm or more and 30 μm or less from the surface opposite to the ceramic member is 70 mgf / μm 2 More than 85mgf / μm 2 Since the hardness is within the range below, the copper member as a whole does not become hard, and when other members are joined to the surface of this copper member, the joining reliability with these other members can be improved.

[0015] The insulating circuit board of the present invention is an insulating circuit board in which a copper plate made of copper or a copper alloy is bonded to the surface of a ceramic substrate, and a Mg solid solution layer in which Mg is dissolved in a Cu matrix is ​​formed at the bonding interface between the ceramic substrate and the copper plate, and the maximum indentation hardness in a region extending from the bonding surface of the ceramic substrate to the copper plate side by 20 μm to 50 μm is 90 mgf / μm. 2 More than 150mgf / μm 2 It is characterized by being within the following range:

[0016] According to the insulating circuit board of the present invention, a Mg solid solution layer in which Mg is dissolved in a Cu matrix is ​​formed at the bonding interface between the ceramic substrate and the copper plate, and the maximum indentation hardness in a region extending from the bonding surface of the ceramic substrate to the copper plate side by 20 μm to 50 μm is 90 mgf / μm. 2 As a result, the copper in the vicinity of the bonding interface is sufficiently melted to generate a liquid phase, and the ceramic substrate and the copper plate are firmly bonded together. On the other hand, the maximum indentation hardness in the aforementioned region is 150 mgf / μm 2 Since the hardness is kept below 0.1%, the vicinity of the bonding interface is not unnecessarily hard, and the occurrence of cracks during thermal cycle loading can be suppressed. Therefore, an insulating circuit board having high bonding strength and particularly excellent thermal cycle reliability can be obtained.

[0017] In the insulating circuit board of the present invention, the average indentation hardness in a region extending from the bonding surface of the ceramic substrate to the copper plate side by 20 μm to 50 μm is 80 mgf / μm. 2 More than 140mgf / μm 2 It is preferable that the content is within the following range: In this case, the average indentation hardness in the region from the bonding surface of the ceramic substrate to the copper plate side of 20 μm to 50 μm is 80 mgf / μm. 2 More than 140mgf / μm 2 Since the content is within the following range, the ceramic substrate and the copper plate are reliably and firmly bonded together by Mg, and the bonded interface is further prevented from becoming hard. Therefore, an insulating circuit board having high bonding strength and particularly excellent thermal cycle reliability can be obtained.

[0018] In the insulating circuit board of the present invention, the average indentation hardness in a region extending from the surface of the copper plate bonded to the ceramic substrate opposite the ceramic substrate to the ceramic substrate by 10 μm or more and 30 μm or less toward the ceramic substrate is 70 mgf / μm. 2 More than 85mgf / μm 2 It is preferable that the content is within the following range: In this case, the average indentation hardness in a region of 10 μm to 30 μm from the surface of the copper plate opposite to the ceramic substrate is 70 mgf / μm. 2 More than 85mgf / μm 2Since the hardness is within the range below, the copper plate as a whole does not become hard, and when other members are joined to the surface of the copper plate, the joining reliability with these other members can be improved. Effect of the Invention

[0019] According to the present invention, it is possible to provide a copper / ceramic bonded body that can suppress the occurrence of cracks in a ceramic member even when subjected to severe thermal cycles and has excellent thermal cycle reliability, and an insulated circuit board made of this copper / ceramic bonded body. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a schematic explanatory diagram of a power module using an insulating circuit board according to an embodiment of the present invention. [Diagram 2] 3 is an enlarged explanatory view of a bonding interface between a circuit layer and a metal layer of the insulating circuit board according to the embodiment of the present invention and a ceramic substrate. FIG. [Diagram 3] FIG. 2 is a flow diagram of a method for manufacturing an insulating circuit board according to an embodiment of the present invention. [Figure 4] 1A to 1C are schematic explanatory diagrams of a method for producing an insulating circuit board according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, an embodiment of the present invention will be described with reference to the accompanying drawings. The copper / ceramic bonded body according to this embodiment is an insulating circuit board 10 formed by bonding a ceramic substrate 11 as a ceramic member made of ceramics to a copper plate 22 (circuit layer 12) and a copper plate 23 (metal layer 13) as copper members made of copper or a copper alloy. Fig. 1 shows a power module 1 including the insulating circuit board 10 according to this embodiment.

[0022] This power module 1 includes an insulating circuit board 10 having a circuit layer 12 and a metal layer 13 arranged thereon, a semiconductor element 3 bonded to one surface of the circuit layer 12 (the upper surface in FIG. 1) via a bonding layer 2, and a heat sink 5 arranged on the other side of the metal layer 13 (the lower side in FIG. 1).

[0023] The semiconductor element 3 is made of a semiconductor material such as Si. The semiconductor element 3 and the circuit layer 12 are bonded to each other via a bonding layer 2. The bonding layer 2 is made of, for example, a Sn--Ag based, Sn--In based, or Sn--Ag--Cu based solder material.

[0024] The heat sink 5 is for dissipating heat from the insulating circuit board 10. The heat sink 5 is made of copper or a copper alloy, and in this embodiment, is made of phosphorus deoxidized copper. The heat sink 5 is provided with a flow path for a cooling fluid to flow. In this embodiment, the heat sink 5 and the metal layer 13 are joined by a solder layer 7 made of a solder material. The solder layer 7 is made of, for example, a Sn-Ag based, Sn-In based, or Sn-Ag-Cu based solder material.

[0025] As shown in FIG. 1, the insulating circuit board 10 of this embodiment includes a ceramic substrate 11, a circuit layer 12 disposed on one surface (the upper surface in FIG. 1) of the ceramic substrate 11, and a metal layer 13 disposed on the other surface (the lower surface in FIG. 1) of the ceramic substrate 11.

[0026] The ceramic substrate 11 is made of silicon nitride (Si 3 N 4 ), Aluminum Nitride (AlN), Alumina (Al 2 O 3In this embodiment, the ceramic substrate 11 is made of aluminum nitride (AlN), which has particularly excellent heat dissipation properties. The thickness of the ceramic substrate 11 is set within a range of, for example, 0.2 mm to 1.5 mm, and in this embodiment, it is set to 0.635 mm.

[0027] As shown in FIG. 4, the circuit layer 12 is formed by bonding a copper plate 22 made of copper or a copper alloy to one surface (the upper surface in FIG. 4) of a ceramic substrate 11. In this embodiment, the circuit layer 12 is formed by bonding a rolled sheet of oxygen-free copper to the ceramic substrate 11. The thickness of the copper plate 22 that becomes the circuit layer 12 is set within a range of 0.1 mm to 2.0 mm, and is set to 0.6 mm in this embodiment.

[0028] As shown in FIG. 4, the metal layer 13 is formed by joining a copper plate 23 made of copper or a copper alloy to the other surface (the lower surface in FIG. 4) of the ceramic substrate 11. In this embodiment, the metal layer 13 is formed by bonding a rolled sheet of oxygen-free copper to the ceramic substrate 11. The thickness of the copper plate 23 that becomes the metal layer 13 is set within a range of 0.1 mm to 2.0 mm, and is set to 0.6 mm in this embodiment.

[0029] Here, at the bonding interface between the ceramic substrate 11 and the circuit layer 12 (metal layer 13), as shown in FIG. 2, an Mg solid solution layer 31 in which Mg is dissolved in the Cu matrix is ​​formed. The Mg solid solution layer 31 is a region where the Mg concentration is 0.01 atomic % or more and 6.9 atomic % or less, when the bonding interface between the circuit layer 12 (metal layer 13) and the ceramic substrate 11 is quantitatively analyzed by observing a region (400 μm long × 600 μm wide) including the bonding interface at a magnification of 200 times and an acceleration voltage of 15 kV using an EPMA device (JXA-8539F manufactured by JEOL Ltd.). Cu concentration + Mg concentration = 100 atomic %.

[0030] In the insulating circuit board 10 according to the present embodiment, as shown in FIG. 2, the maximum indentation hardness in a region E1 extending from the bonding surface of the ceramic substrate 11 to the circuit layer 12 (metal layer 13) side by 20 μm to 50 μm is 90 mgf / μm. 2 More than 150mgf / μm 2 It is within the following range: In this embodiment, the average indentation hardness in the above-mentioned region E1 is 80 mgf / μm 2 More than 140mgf / μm 2 It is preferable that the content is within the following range:

[0031] In this embodiment, the average indentation hardness in a region E2 extending from the surface of the circuit layer 12 formed on one side of the ceramic substrate 11 and the metal layer 13 formed on the other side of the ceramic substrate 11 to the ceramic substrate 11 side by 10 μm to 30 μm is 70 mgf / μm. 2 More than 85mgf / μm 2 It is preferable that the content is within the following range:

[0032] A method for manufacturing the insulating circuit board 10 according to this embodiment will be described below with reference to FIGS.

[0033] (Mg placement process S01) First, a ceramic substrate 11 is prepared, and as shown in FIG. 4, Mg is placed between the ceramic substrate 11 and a copper plate 22 that will become the circuit layer 12, and between the ceramic substrate 11 and a copper plate 23 that will become the metal layer 13. In this embodiment, Mg foil 25 is disposed between the copper plate 22 that will become the circuit layer 12 and the ceramic substrate 11, and between the copper plate 23 that will become the metal layer 13 and the ceramic substrate 11. Here, in the Mg arrangement step S01, the amount of Mg arranged is 0.34 mg / cm 2 More than 4.35mg / cm 2 Within the following range. The amount of Mg placed is 0.52 mg / cm2 More preferably, it is 0.69 mg / cm or more. 2 On the other hand, the amount of Mg to be placed is preferably 3.48 mg / cm or more. 2 It is preferable that the concentration is 2.61 mg / cm or less. 2 It is even more preferable that:

[0034] (Lamination process S02) Next, the copper plate 22 and the ceramic substrate 11 are laminated with the Mg foil 25 interposed therebetween, and the ceramic substrate 11 and the copper plate 23 are laminated with the Mg foil 25 interposed therebetween.

[0035] (Joining process S03) Next, the laminated copper plate 22, Mg foil 25, ceramic substrate 11, Mg foil 25, and copper plate 23 are pressed in the lamination direction and heated in a vacuum furnace to bond the copper plate 22, ceramic substrate 11, and copper plate 23 together.

[0036] Here, the holding temperature in the bonding step S03 is preferably within a range of 700° C. to 850° C. The temperature integral value S during the temperature rise process from 670° C. to the holding temperature and during the holding process at the heating temperature is preferably within a range of 30° C. h to 500° C. h. Moreover, the pressure load P in the joining step S03 is preferably set within a range of 0.09 MPa or more and 1.96 MPa or less.

[0037] Furthermore, the product P×S of the applied load P and the temperature integral value S is preferably within the range of 30°C·h·MPa to 650°C·h·MPa. By setting the product P×S of the pressure load P and the temperature integral value S within the above-mentioned range, the discharge state of the liquid phase generated during joining can be adjusted, and the diffusion state of Mg into the copper plates 22, 23 can be controlled.

[0038] Furthermore, the degree of vacuum in the furnace during the bonding process S03 is 1×10 -6 Pa or more 5×10 -2 It is preferable to set the range to 0.1 Pa or less. The cooling rate during cooling is preferably within the range of 2° C. / min to 20° C. / min, where the cooling rate is the average value of the cooling rate from the holding temperature to 670° C.

[0039] As described above, the insulating circuit board 10 of this embodiment is manufactured by the Mg arrangement step S01, the lamination step S02, and the bonding step S03.

[0040] (Heat sink bonding process S04) Next, heat sink 5 is bonded to the other surface side of metal layer 13 of insulating circuit board 10. Insulated circuit board 10 and heat sink 5 are laminated with a solder material interposed therebetween and loaded into a heating furnace, where insulating circuit board 10 and heat sink 5 are solder-joined via solder layer 7 .

[0041] (Semiconductor element bonding process S05) Next, the semiconductor element 3 is joined to one surface of the circuit layer 12 of the insulating circuit board 10 by soldering. Through the above-described steps, the power module 1 shown in FIG. 1 is manufactured.

[0042] According to the insulating circuit board 10 (copper / ceramic bonded body) of the present embodiment configured as described above, an Mg solid solution layer 31 in which Mg is dissolved in the Cu matrix is ​​formed at the bonding interface between the ceramic substrate 11 and the circuit layer 12 (metal layer 13). The maximum indentation hardness in a region E1 extending from the bonding surface of the ceramic substrate 11 to the circuit layer 12 (metal layer 13) side by 20 μm to 50 μm is 90 mgf / μm. 2 As described above, the copper in the vicinity of the bonding interface is sufficiently melted to generate a liquid phase, and the ceramic substrate 11 and the circuit layer 12 (metal layer 13) are firmly bonded together. On the other hand, the maximum indentation hardness in the aforementioned region E1 is 150 mgf / μm 2 Since the hardness is kept below 0.1%, the vicinity of the bonding interface is not unnecessarily hard, and the occurrence of cracks during thermal cycle loading can be suppressed. Therefore, it is possible to obtain an insulating circuit board 10 having high bonding strength and particularly excellent thermal cycle reliability.

[0043] In order to further improve the thermal cycle reliability, the maximum indentation hardness in a region E1 extending from the bonding surface of the ceramic substrate 11 to the circuit layer 12 (metal layer 13) side by 20 μm to 50 μm is set to 145 mgf / μm. 2 It is preferable that the density is less than 135 mgf / μm 2 It is more preferable to set it as follows: On the other hand, in order to bond the ceramic substrate 11 and the circuit layer 12 (metal layer 13) more reliably, the maximum indentation hardness in a region E1 extending from the bonding surface of the ceramic substrate 11 to the circuit layer 12 (metal layer 13) side by 20 μm to 50 μm is set to 100 mgf / μm. 2 More preferably, it should be 110 mgf / μm or more. 2 More preferably, it is equal to or greater than this.

[0044] In addition, in the insulating circuit board 10 of this embodiment, the average indentation hardness in a region E1 extending from the bonding surface of the ceramic substrate 11 to the circuit layer 12 (metal layer 13) side by 20 μm to 50 μm is 80 mgf / μm. 2 More than 140mgf / μm 2 When the content is within the following range, Mg ensures that the ceramic substrate 11 and the circuit layer 12 (metal layer 13) are firmly bonded together, and hardening of the bonded interface is further suppressed. Therefore, it is possible to obtain an insulating circuit board 10 having high bonding strength and particularly excellent thermal cycle reliability.

[0045] The lower limit of the average value of the indentation hardness in the region E1 from the bonding surface of the ceramic substrate 11 to the circuit layer 12 (metal layer 13) side by 20 μm to 50 μm is 85 mgf / μm. 2 More preferably, it is 90 mgf / μm or more. 2 The upper limit of the average value of the indentation hardness in the above-mentioned region E1 is 135 mgf / μm2 More preferably, it is 125 mgf / μm or less. 2 It is even more preferable that:

[0046] Furthermore, in the insulating circuit board 10 of this embodiment, the average indentation hardness in a region E2 extending from the surface of the circuit layer 12 (metal layer 13) opposite the ceramic substrate 11 to the ceramic substrate 11 side by 10 μm or more and 30 μm or less is 70 mgf / μm. 2 More than 85mgf / μm 2 When the temperature is within the range below, the entire circuit layer 12 (metal layer 13) does not harden, and when other components are joined to the surface of the circuit layer 12 (metal layer 13), the joining reliability with these other components can be improved.

[0047] The upper limit of the average value of the indentation hardness in a region E2 from the surface of the circuit layer 12 (metal layer 13) opposite to the ceramic substrate 11 to the ceramic substrate 11 side by 10 μm or more and 30 μm or less is 83 mgf / μm 2 More preferably, it is 80 mgf / μm or less. 2 It is even more preferable that:

[0048] Although the embodiment of the present invention has been described above, the present invention is not limited to this, and can be modified as appropriate without departing from the technical concept of the invention. For example, in the present embodiment, a power module is configured by mounting a semiconductor element on an insulating circuit board, but the present invention is not limited to this. For example, an LED module may be configured by mounting an LED element on a circuit layer of an insulating circuit board, or a thermoelectric module may be configured by mounting a thermoelectric element on a circuit layer of an insulating circuit board.

[0049] In addition, in the insulating circuit board of the present embodiment, the ceramic substrate is described as being made of aluminum nitride (AlN), but the present invention is not limited to this. For example, the ceramic substrate may be made of alumina (Al 2 O 3 ), silicon nitride (Si 3 N4 ) or other ceramic substrates may be used.

[0050] Furthermore, in this embodiment, the circuit layer is described as being formed by bonding a rolled sheet of oxygen-free copper to a ceramic substrate, but this is not limited to this, and the circuit layer may be formed by bonding copper pieces punched out of a copper plate to a ceramic substrate in a state in which the copper pieces are arranged in a circuit pattern. In addition, in this embodiment, the Mg foil is disposed between the ceramic substrate and the copper plate, but the present invention is not limited to this. As long as a bonding material is disposed between the ceramic substrate and the copper plate, Mg may be disposed on the bonding surface of the ceramic substrate, or on the bonding surface of the copper plate. Mg may also be disposed by sputtering or vapor deposition on the ceramic substrate and / or the copper plate. A clad material of copper plate and Mg foil can also be used. Mg powder and / or MgH 2 The Mg can also be placed between the ceramic substrate and the copper plate using a paste containing the powder. EXAMPLES

[0051] The results of experiments carried out to confirm the effects of the present invention will be described below.

[0052] First, a ceramic substrate (40 mm × 40 mm) was prepared as shown in Table 1. The thickness of the substrate was 40 mm × 40 mm for AlN and Al 2 O 3 0.635mm, Si 3 N 4 was set to 0.32 mm. In addition, copper plates that would become the circuit layers and metal layers were prepared, each of which was made of oxygen-free copper and had a size of 37 mm×37 mm and a thickness shown in Table 1.

[0053] The copper plate and the ceramic substrate were then bonded under the conditions shown in Table 1 to obtain insulated circuit substrates (copper / ceramic bonded bodies) of Invention Examples 1 to 9 and Comparative Example 1. The degree of vacuum in the vacuum furnace during bonding was 2×10 -3 The name was Pa.

[0054] The obtained insulating circuit board (copper / ceramic bonded body) was evaluated for indentation hardness and thermal cycle reliability (cracking of ceramic substrate, bonding rate after thermal cycle load) as follows.

[0055] (Indentation hardness) The obtained insulating circuit board (copper / ceramic bonded body) was cut in the lamination direction, and the indentation hardness in the bonding interface between the ceramic substrate and the circuit layer and metal layer in a region E1 extending from 20 μm to 50 μm from the bonding surface of the ceramic substrate toward the circuit layer and metal layer was measured and calculated at four points in one field of view, for a total of 40 points in five fields of view, and the maximum and average values ​​were calculated. In addition, the indentation hardness in the region E2 extending from the surface of the circuit layer and metal layer opposite the ceramic substrate to the ceramic substrate side of 10 μm or more and 30 μm or less was measured at four points in one field of view, for a total of 40 points in five fields of view, and the average value was calculated.

[0056] (Reliability of thermal cycles) The above-mentioned insulating circuit board was subjected to a thermal shock tester (TSA-72ES manufactured by Espec Corp.) to apply a thermal shock cycle in the gas phase, and the presence or absence of ceramic cracks was judged by SAT inspection. The thermal shock cycle conditions were set as follows according to the material of the ceramic board. AlN,Al 2 O 3 In this case: -40℃ x 15 min ←→ 150℃ x 15 min, SAT inspection every 100 cycles up to 1000 cycles. S 3 N 4 In this case: -40℃ x 15 min ←→ 150℃ x 15 min, SAT inspection every 200 cycles up to 3000 cycles.

[0057] (Joining rate) The bonding ratio before and after the above-mentioned thermal cycle load was evaluated as follows. When cracks were found in the ceramic substrate, the bonding ratio at that time was evaluated. The bonding rate of the interface between the ceramic substrate and the copper plate (circuit layer and metal layer) of the insulated circuit board was evaluated using an ultrasonic flaw detector (FineSAT FSP8V manufactured by Hitachi Power Solutions Co., Ltd.), and the bonding rate was calculated using the following formula.

[0058] Here, the initial bonding area refers to the area to be bonded before bonding, that is, the area of ​​the circuit layer and the metal layer (37 mm×37 mm) in this embodiment. (Bonding rate) = {(initial bonding area) - (peeling area)} / (initial bonding area) In the binarized image of the ultrasonic inspection image, the peeling is shown as a white area within the joint, and the area of ​​this white area was taken as the peeling area.

[0059] [Table 1]

[0060] [Table 2]

[0061] First, invention examples 1-3, which use AlN as the ceramic substrate, will be compared with comparative examples 1 and 2. In Comparative Example 1, the maximum indentation hardness in the region from 20 μm to 50 μm from the bonding surface of the ceramic substrate to the copper plate side was 86.3 mgf / μm. 2 In the thermal cycle test, cracks occurred 300 times, and the bonding rate after thermal cycle loading was low at 64.5%. In Comparative Example 2, the maximum indentation hardness in the region from 20 μm to 50 μm from the bonding surface of the ceramic substrate to the copper plate side was 170.5 mgf / μm. 2 In a thermal cycle test, cracks occurred 200 times.

[0062] In contrast, in Example 1-3 of the present invention, the maximum indentation hardness in the region from the joining surface of the ceramic substrate to the copper plate side, which is 20 μm to 50 μm, is 90 mgf / μm. 2 More than 150mgf / μm 2 The range is as follows: In the thermal cycle test, the number of times cracks occurred was 700 to 1000 times, and the bonding rate after thermal cycle loading was 90.6 to 98.9%, demonstrating excellent thermal cycle reliability.

[0063] Next, we used Si as a ceramic substrate. 3 N 4 The present invention examples 4-6 using the above are compared with comparative examples 3 and 4. In Comparative Example 3, the maximum indentation hardness in the region from 20 μm to 50 μm from the bonding surface of the ceramic substrate to the copper plate side was 87.3 mgf / μm. 2 In the thermal cycle test, cracks occurred 1,200 times, and the bonding rate after thermal cycle loading was low at 52.5%. In Comparative Example 4, the maximum indentation hardness in the region from 20 μm to 50 μm from the bonding surface of the ceramic substrate to the copper plate side was 179.1 mgf / μm. 2 The number of times cracks occurred during thermal cycle testing was 1,400.

[0064] In contrast, in Example 4-6 of the present invention, the maximum indentation hardness in the region from the joining surface of the ceramic substrate to the copper plate side, which is 20 μm to 50 μm, is 90 mgf / μm. 2 More than 150mgf / μm 2 The range is as follows: In the thermal cycle test, the number of times cracks occurred exceeded 2,400 to 3,000 times, and the bonding rate after thermal cycle loading was 95.4 to 97.9%, demonstrating excellent thermal cycle reliability.

[0065] Next, Al was used as a ceramic substrate. 2 O 3 The present invention examples 7 and 8 using the above are compared with the comparative example 5. In Comparative Example 5, the maximum indentation hardness in the region from 20 μm to 50 μm from the bonding surface of the ceramic substrate to the copper plate side was 158.2 mgf / μm. 2 In a thermal cycle test, cracks occurred 300 times.

[0066] In contrast, in Examples 7 and 8 of the present invention, the maximum indentation hardness in the region from the bonding surface of the ceramic substrate to the copper plate side, which is 20 μm to 50 μm, was 90 mgf / μm. 2 More than 150mgf / μm 2 The range is as follows: In the thermal cycle test, the number of cracks that occurred was 800 to 900, and the bonding rate after thermal cycle loading was 96.5 to 97.7%, demonstrating excellent thermal cycle reliability.

[0067] From the results of the above confirmatory experiments, it was confirmed that according to the present invention, even when subjected to severe thermal cycles, the occurrence of cracks in the ceramic members can be suppressed, and an insulated circuit board (copper / ceramic bonded body) with excellent thermal cycle reliability can be provided. [Explanation of symbols]

[0068] 10 Insulated circuit board (copper / ceramic joint) 11 Ceramic substrate (ceramic component) 12 Circuit layer (copper material) 13 Metal layer (copper material) 31 Mg solid solution layer

Claims

1. A copper / ceramic bonded body obtained by bonding a copper member made of copper or a copper alloy to a ceramic member, a Mg solid solution layer in which Mg is dissolved in a Cu matrix is ​​formed at a joint interface between the ceramic member and the copper member, The maximum indentation hardness in the region from the joining surface of the ceramic member to the copper member side by 20 μm to 50 μm is 90 mgf / μm. 2 More than 150mgf / μm 2 A copper / ceramic bonded body, characterized in that the bonding strength is within the following range.

2. The average indentation hardness in the region from the joining surface of the ceramic member to the copper member side of 20 μm to 50 μm is 80 mgf / μm. 2 140 mgf / μm or more 2 2. The copper / ceramic bonded body according to claim 1, characterized in that the following range is satisfied:

3. The average indentation hardness in a region from the surface of the copper member opposite to the ceramic member to the ceramic member by 10 μm to 30 μm toward the ceramic member is 70 mgf / μm 2 More than 85mgf / μm 2 3. The copper / ceramic bonded body according to claim 1, wherein the copper / ceramic bond is within the following range:

4. An insulating circuit board having a ceramic substrate and a copper plate made of copper or a copper alloy bonded to the surface thereof, a Mg solid solution layer in which Mg is dissolved in a Cu matrix is ​​formed at a bonding interface between the ceramic substrate and the copper plate, The maximum indentation hardness in the region from the bonding surface of the ceramic substrate to the copper plate side, which is 20 μm to 50 μm, is 90 mgf / μm. 2 More than 150mgf / μm 2 An insulating circuit board characterized by being within the following range.

5. The average indentation hardness in the region from the bonding surface of the ceramic substrate to the copper plate side of 20 μm to 50 μm is 80 mgf / μm. 2 140 mgf / μm or more 2 5. The insulating circuit board according to claim 4, characterized in that the insulating circuit board has a thickness within the following range.

6. The average indentation hardness in a region from the surface of the copper plate bonded to the ceramic substrate opposite the ceramic substrate to the ceramic substrate by 10 μm to 30 μm toward the ceramic substrate is 70 mgf / μm 2 More than 85mgf / μm 2 6. The insulating circuit board according to claim 4, wherein the insulating circuit board has a thickness within the following range:

Citation Information

Patent Citations

  • Method for manufacturing substrate for power module, method for manufacturing substrate for power module with heat sink, and method for manufacturing power module

    JP2014222788A

  • Copper / ceramic joint, insulated circuit board, copper / ceramic joint producing method, insulated circuit board producing method

    JP2021035901A

  • Copper / ceramic assembly, insulation circuit board, method for manufacturing copper / ceramic assembly, and method for manufacturing insulation circuit board

    JP2021091596A

  • Copper / ceramic bonded body, insulating circuit board, manufacturing method of copper / ceramic bonded body, and manufacturing method of insulating circuit board

    JP2021100896A

  • circuit board

    JP3211856B2